Hubungan Pengetahuan Tentang Diet Sehat Dengan Sikap Lansia Dalam Mencegah Diabetes Melitus di Desa Sumber Mufakat Kecamatan Kabanjahe Tahun 2023 - Herianto Bangun; Harry Dito Meliala (Lembaga Pengembangan Kinerja Dosen, 2023)
The dominant problem that requires special attention in the elderly is a decrease in health and a problem of poor nutritional intake which can be caused by a lack of knowledge or due to decreased functions of the digestive organs due to the aging process. Bivariate data analysis was used to see the significance of the relationship between the independent variable and the dependent variable which was carried out using the Chi-square (x^2) statistical test. If Ρ=(0.05) > Chi-Square results then Ho is accepted and Ha is rejected, meaning there is no relationship between the research results and theory. If ρ=(0.05) < from the Chi-Square results then Ho is accepted and Ha is rejected, meaning there is a relationship between the research results and theory. The results of the analysis showed that of the 36 respondents the majority had insufficient knowledge about a healthy diet as many as 18 respondents (50.0%), respondents who had sufficient knowledge about a healthy diet as many as 17 respondents (47.2%) and respondents who had good knowledge about diet healthy as much as 1 respondent (2.8%). The research obtained in Sumber Mufakat Village, Kabanjahe District, shows that the majority are elderly (60-74) as many as 20 respondents (55.6%), the majority have basic education (SD-SMP) as many as 33 respondents (91.66%) , the majority worked as farmers as many as 31 respondents (86.11%), the majority received information from health workers as many as 22 respondents (61.1%), the majority had less knowledge as many as 18 respondents (50.0%) and the majority had a positive attitude as many as 20 respondents (55.6%), where the level of education greatly influences a person's level of knowledge. This shows that the higher a person's level of education, the higher their level of knowledge. The majority of elderly people have less knowledge about a healthy diet, as many as 18 respondents (50.0%). preventing diabetes mellitus where the better the knowledge of the elderly, the better the attitude of the elderly in preventing diabetes mellitus in Sumber Mufakat Village, Kabanjahe District, 2018 with a p value = 0.00.